OECS experience with structural adjustment: case studies: Dominica, St. Lucia & St. Vincent - Bowen, Sherene ([s.n.] [S.l.], 1992)
Looks at the structure of the economies before the structural adjustment programme; the policy actions taken in the effort as a result of the structural adjustment programme; the economic performance while under the structural adjustment programme to the present; and finally presents a general discussion of the issues concerning the implementation of structural adjustment.